Impact of educational interventions on the prevention of influenza: A systematic review - Nasiri, Mohammad Javad; Danaei, Bardia; Deravi, Niloofar; Chirani, Alireza Salimi; Bonjar, Amir Hashem Shahidi; Khoshgoftar, Zohreh; Karimi, Forouzan (Frontiers in Public Health, 2022)
Introduction: Seasonal influenza, a contagious viral disease affecting the upper respiratory tract, circulates annually, causing considerable morbidity and mortality. The present study investigates the effectiveness of educational interventions to prevent influenza. Methods: We searched PubMed/Medline, Embase, and Cochrane Controlled Register of Trials (CENTRAL) for relevant clinical studies up to March 1 2022. The following terms were used: “influenza”, “flu”, “respiratory infection”, “prevent”, “intervention”, and “education”. Results: Out of 255 studies, 19 types of research satisfied the inclusion criteria and were included in our study: 11 parallel randomized controlled trials (RCT) studies, two cross-over RCT studies, two cohort studies, and four quasi-experimental studies. A total of approximately 125000 adults (18 years old or above) and 56000 children were evaluated. Educational sessions and reminders were the most common interventions. The measured outcomes were vaccination rates, the incidence of respiratory tract infection (RTI), and preventive behaviors among participants. 17 out of 19 articles showed a significant association between educational interventions and the outcomes. Conclusions: The included studies in the current systematic review reported the efficacy of health promotion educational interventions in improving knowledge and preventive behaviors, vaccination rates, and decreased RTI incidence regardless of the type of intervention and the age of cases.